RAISING OF RABBIT HYPERIMMUNE SERUM FOR LABORATORY DIAGNOSIS OF PESTE DES PETITS RUMINANTS (PPR) VIRUS - M. Asim; A. Rashid; A. Hussain; M. S. Noor (Journal of Animal and Plant Sciences, 2008)
Agar gel immunodiffusion (AGID) test is a simple and rapid method for the diagnosis of Peste des petits ruminants (PPR) which requires the preparation of potent specific hyperimmune serum. This study deals with the raising of hyperimmune serum against PPR virus in rabbit. Four different inocula included PPR vaccine reconstituted in phosphate buffer saline, PPR antigen suspended in phosphate buffer saline, PPR vaccine in oil adjuvant and PPR antigen in oil adjuvant were used. All inocula were inoculated at different intervals and concluded that inoculum contained PPR antigen in oil adjuvant provoked better immune response against PPR virus in rabbits.
Keywords: Hyperimmune serum; PPR; Rabbits.